2018
DOI: 10.1002/elan.201800255
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biomass Derived Carbon Quantum Dots for Highly Sensitive and Selective Detection of Hydrazine

Abstract: We report for the first time, carbon quantum dots (CQD) based highly sensitive and selective electrochemical sensor for detection of hydrazine. CQD was synthesized by pyrolysis method using a natural precursor, chia seeds. The sensing ability was studied in terms of oxygen‐rich functional groups present on the surface of CQD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This "bottom-up" technique could be done by many methods such as hydrothermal, microwave-assisted method, pyrolysis, and ultrasonic and acid dehy-dration methods. Additionally, recent studies reported emerging, low cost raw materials used in the preparation of C-dots applied in electrochemical sensors such as biomasses and biochar [25,26], which shows the variety of starting materials that can be used for C-dot synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This "bottom-up" technique could be done by many methods such as hydrothermal, microwave-assisted method, pyrolysis, and ultrasonic and acid dehy-dration methods. Additionally, recent studies reported emerging, low cost raw materials used in the preparation of C-dots applied in electrochemical sensors such as biomasses and biochar [25,26], which shows the variety of starting materials that can be used for C-dot synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, major limitations of the above‐mentioned techniques are their high cost and complexity, time consuming sample pre‐treatment. In this regard, electrochemical sensors have increased significant attention on account of their low‐cost, in‐situ detection of analytes, high sensitivity, quick and user‐friendly operation modes .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazine structures are characterized by a single covalent N-N bond which carries from one up to four alkyl or aryl substituents. Hydrazines are highly toxic for human health, and, among their wide range of applications, CDs have been adopted as a fluorescent sensor for this class of compounds [47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%